The Corner House Girls Among the Gypsies : How They Met, What Happened, and How It Ended - Hill, Grace Brooks; Gooch, Thelma, 1895-1973 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Corner House Girls Among the Gypsies" by Grace Brooks Hill is a novel written in the early 20th century. The book follows the delightful escapades of the Corner House girls, particularly Tess and Dot, as they encounter Gypsies, stumble upon a mysterious silver bracelet, and navigate the joys and challenges of childhood adventures. As the narrative unfolds, themes of honesty, friendship, and youthful imagination are explored against the backdrop of a whimsical journey. At the start of the story, we are introduced to the lively dynamic among the Corner House girls and their interactions with Sammy Pinkney, a local boy. The excitement begins when Tess and Dot purchase a colorful basket from two Gypsy women, only to discover a silver bracelet inside it, sparking a moral dilemma about whether to keep it or return it to the rightful owners. The opening chapters set the tone for a narrative rich in playful banter, the innocence of childhood, and hints of intrigue regarding the Gypsies and the bracelet, prompting the characters to embark on a quest filled with unexpected encounters and decisions that will lead them into further adventures. (This is an automatically generated summary.)
Release date is 2011-06-12
E-text prepared by Roger Frank and the Online Distributed Proofreading Team (http://www.pgdp.net)
Keywords: Runaway children -- Juvenile fiction; Sisters -- Juvenile fiction; Families -- Juvenile fiction; Romanies -- Juvenile fiction; First loves -- Juvenile fiction; Jewelry -- Juvenile fiction